(untitled) (Tejganga Darpan, 2026)
Teaching and learning situation faced a notable shift after the Pandemic in Nepal as teaching and learning was completely book based, the changed scenario not only altered teaching context, it reformed teachers’ identity. This study explores stories of two English language teachers who changed their practiced integrating digital literacy skill and transformed their identity. This study employed narrative inquiry as a method and interview guideline is the prime tool to collect information. Information generated is analyzed using Wenger (1998) theory of identity formation. The study finding revealed that teachers’ day to day engagement can reforms their identity. Teachers’ digital integration in the teaching and learning process valued teachers’ engagement. They are identified as a successful digital friendly teacher, innovative teacher in the professional space. This study finding contributes all the teachers who are willing to integrate digital tools, materials and platforms to shift teaching addressing the demand of 21st century learner.